2023
DOI: 10.1038/s41586-023-06038-z
|View full text |Cite|
|
Sign up to set email alerts
|

Structural evidence for intermediates during O2 formation in photosystem II

Abstract: In natural photosynthesis, the light-driven splitting of water into electrons, protons and molecular oxygen forms the first step of the solar-to-chemical energy conversion process. The reaction takes place in photosystem II, where the Mn4CaO5 cluster first stores four oxidizing equivalents, the S0 to S4 intermediate states in the Kok cycle, sequentially generated by photochemical charge separations in the reaction center and then catalyzes the O–O bond formation chemistry1–3. Here, we report room temperature s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
54
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 62 publications
(102 reference statements)
6
54
0
Order By: Relevance
“…Thinking outside the box strategies, such as ultrasound and magnetic field-assisted water splitting, are promising in the OER field. , In Nature, cyanobacteria, algae, and plants utilize a similar oxygen-evolving complex (OEC). This biocatalyst is situated in Photosystem II, a membrane-protein complex that functions as a light-driven water oxidase in oxygenic photosynthesis. The biological OEC, an Mn–Ca cluster, oxidizes water with a notably low overpotential (20 mV) and a high turnover frequency, releasing 25–90 molecules of O 2 per second. , According to a mechanism widely accepted by Kok, OEC can exist in five states (S 0 to S 4 ) postcharge accumulation based on Mn­(III)/Mn­(IV). The system progresses from the most reduced state, S 0 , to the most oxidized state, S 4 , as photons are captured by photosystem II. , The unstable S 4 state reacts with water to produce O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Thinking outside the box strategies, such as ultrasound and magnetic field-assisted water splitting, are promising in the OER field. , In Nature, cyanobacteria, algae, and plants utilize a similar oxygen-evolving complex (OEC). This biocatalyst is situated in Photosystem II, a membrane-protein complex that functions as a light-driven water oxidase in oxygenic photosynthesis. The biological OEC, an Mn–Ca cluster, oxidizes water with a notably low overpotential (20 mV) and a high turnover frequency, releasing 25–90 molecules of O 2 per second. , According to a mechanism widely accepted by Kok, OEC can exist in five states (S 0 to S 4 ) postcharge accumulation based on Mn­(III)/Mn­(IV). The system progresses from the most reduced state, S 0 , to the most oxidized state, S 4 , as photons are captured by photosystem II. , The unstable S 4 state reacts with water to produce O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…By combining high-resolution XAS data with QM calculations, we have clearly shown that recent controversies regarding the nature of the S 3 state can be rigorously resolved and that presence of either peroxo or oxo/oxyl level intermediate can be ruled out. An all-Mn(IV) S 3 state should be considered as the starting intermediate in the interpretation of experimental data on the S 3 to S 0 transition. , Overall, the results of this work clearly show Mn-based oxidation during the S 2 to S 3 transition and constrain the possible mechanisms of the formation of the O–O bond to those that initiate after the final light-driven oxidation. Beyond the importance for biological water oxidation, the cumulative metal-centered storage of oxidizing equivalents supported by the present study directs our attention to synthetic water oxidation catalysts that leverage multimetallic cooperativity.…”
Section: Discussionmentioning
confidence: 99%
“…Of note is that, in the natural photosystem II (PS II), the water oxidation occurs through first storing four oxidizing equivalents into the oxygen-evolving complex (OEC) featuring the Mn 4 CaO 5 reaction center and then catalyzing the O–O bond formation. 9–11 Inspired by the OEC in PS II, great efforts have been devoted to the investigation of molecular and supramolecular WOCs being structurally and functionally analogous to the Mn 4 CaO 5 cluster. 12–16…”
Section: Introductionmentioning
confidence: 99%